Climate Justice: Whose Justice? - Ikporukpo, Chris (Advances in Social Sciences Research Journal, 2022)
The increasing literature on climate justice is indicative of the increasing severity and public awareness of the challenge of climate change and the need for action. Generally speaking, the extant literature emphasises climate justice activism during COPs, climate justice movements and their activities, and climate justice activism in specific geographical regions. A case study approach is typical and neglects the actions of non-climate justice movement actors. This approach does not make for generalization on climate justice action. This article analyses the emergence and propagation of climate justice from a global perspective taking into consideration state actors and non-state actors, including non-movement groups and individuals. Varied sources of data are used and the analysis is descriptive and perspective. Rawls’ theory of justice and the resource mobilisation theory provide the theoretical underpinning. State actors, which are commonly analysed as antithetically related to the climate justice movements, play sensitisation and awareness-creation roles through IPCC. Furthermore, State-actors through COP play critical roles negotiating for polluters pay and emission mitigation (net-zero) systems. Non-State actors, including non-formal groups and individuals, have been particularly critical in the fight for climate justice. Their actions have been through songs and poems, pressured mobilisation through protests, strikes and sloganeering, and litigation. Several challenges hinder the enthronement of climate justice. A successful enthronement of climate justice necessitates cooperation between State and non-State actors; which is the basis of the Marrakech Initiative of 2016.